High prevalence of cardiovascular risk factors in adults living in Greece: the EMENO National Health Examination Survey - Touloumi, Giota; Karakosta, Argiro; Kalpourtzi, Natasa; Gavana, Magda; Vantarakis, Apostolos; Kantzanou, Maria; Hajichristodoulou, Christos; Chlouverakis, Grigoris; Trypsianis, Grigoris; Voulgari, Paraskevi V.; Alamanos, Yannis; Makrilakis, Konstantinos; et al. (BMC public health, 2020)
Background Nationwide data on cardiovascular risk factors prevalence is lacking in Greece. This work presents the findings of the national health examination survey EMENO (2013–2016) regarding the prevalence of hypertension, hypercholesterolemia, diabetes, obesity and smoking. Methods A random sample of adults (≥18 years) was drawn by multistage stratified random sampling based on 2011 Census. All EMENO participants with ≥1 measurement of interest [blood pressure (BP), fasting glucose, HbA1c, total cholesterol (TC), Body Mass Index (BMI)] were included. Hypertension was defined as BP ≥ 140/90 mmHg and/or antihypertensive treatment; diabetes as fasting glucose≥126 mg/dL and/or HbA1c ≥ 6.5% or self-reported diabetes; hypercholesterolemia as TC ≥ 190 mg/dL. Sampling weights were applied to adjust for study design and post-stratification weights to match sample age and sex distribution to population one. Non-response was adjusted by inverse probability weighting. Results Of 6006 EMENO participants, 4822 were included (51.5% females, median age:47.9 years). The prevalence of hypertension was 39.2%, higher in men (42.4%) than in women (36.1%); of hypercholesterolemia 60.2%, similar in men (59.5%) and women (60.9%); of diabetes 11.6%, similar men (12.4%) and women (10.9%); of obesity 32.1%, higher in women (33.5% vs 30.2%), although in subjects aged 18–40 year it was higher in men; of current smoking 38.2%, higher in men (44.0%) than in women (32.7%). The prevalence of all risk factors increased substantially with age, except smoking, which followed an inverse U shape. Conclusions The burden of cardiovascular risk factors among Greek adults is alarming. There is considerable preventive potential and actions at health care and societal level are urgently needed.